Meningkatkan Keaktifan Peserta Didik Pada Kelas XI TBG 1 SMKN3 Jember Melalui Aplikasi Google Classroom - Sevi S Addine (Universitas Muhammadiyah Gresik, 2020)
This research is a Classroom Action Research (CAR) which aims to increase the learning activeness of students through the Google Classroom application. The subjects in this study were 33 students of class XI TBG 1 SMK Negeri 3 Jember. Data collection techniques in this research include observation, tests. Active learning through the Google Classroom application is carried out in 2 cycles consisting of the planning stage, the implementation stage, the observation stage and the reflection stage. The results of the study in cycle 1 showed that the class average value obtained was 66.3%, after being given action in cycle II using an innovative learning model, the learning outcomes increased with a class average score of 75% with 31 students who completed. . These results indicate that there is an increase in student learning outcomes using the google classroom application, so it can be concluded that student learning activity also increases.